Daya Saing Usaha Mikro Melalui Sertifkasi Produk Industri Rumah Tangga - Wardhani, Dhiyan Krishna; Harumi, Mellia; Kumolo B, Louis Cahyo; Kristanti, Agnes Indah Suciani; Wijaya, Daniswara Agusta; Pratiwi, Alberta Rika (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2023)
Culinary is an important aspect of developing tourism destinations. Micro, Small, and Medium Enterprises (MSMEs) are the support for food supply that are required to fulfill requirements to ensure consumer food safety by having a Home Industry Food Production Certificate (SPP-IRT). Efforts to fulfill product quality improvements can further increase the competitiveness of micro-business actors. The provisions or requirements for obtaining this permit often make it difficult for MSME players. This program aims to train and assist food MSMEs in obtaining SPP-IRT. The approach used is focus group discussions (FGD), tutorials, nutritional composition testing, and direct assistance in filling out the official IRT permit registration application issued by the government. The activity results showed that 56 food MSMEs who took part in the FGD had received training on good manufacturing practices, processing methods for processed products, and P-IRT ownership. Twelve MSME products already have documents on nutritional content and nutritional adequacy figures, and 13 MSMEs have succeeded in obtaining Home Industry Licensing Certificates, while the rest are still in the form of Business Identification Numbers (NIB), which is the identity that business actors need to have. The nutritional content and P-IRT number can be included on the packaging to gain consumer trust.